Ancient forests and their indicators in urban areas: the role of long-term proximity, area, and distance from the city center - Masiarek, Inez; Witosławski, Piotr; Kiedrzyński, Marcin (Ecological Questions, 2025)
Urban areas are complex and ever-changing systems, whose natural surroundings are profoundly influenced by urbanization processes. In the face of such changes, there is an urgent need to evaluate the state of nature within cities from the perspective of spatial planning and nature conservation. We consider forest specialists, which are unable to colonize new forests rapidly, as indicators of long-standing woodlands in the city area. The main aim of this study was to determine the distribution patterns of forest specialists and to explore their correlation with ancient forests. We hypothesize that it is not just the occurrence of ancient forests that determines the distribution and richness of forest plants. We also explore the so-called ‘adjacent grid permanent forests’; the area of forest-patches, and their location in relation to the city center. Our first task was to examine the changes in the city's forest coverage and pinpoint the location of ancient forests. The study employed historical maps and cartographic works. With the aid of GIS tools, it was possible to depict changes in forest cover over the past 200 years. The distribution of the studied indicator species, overlaid on changing forest cover, unveiled a strong correlation with historical land use. Our findings highlight that both ancient forests and adjacent permanent forests are vital for preserving forest species. Proximity to the city center significantly impacts the occurrence of forest specialists, which are often absent even from areas with ancient forests. However, they may be present despite no detection of ancient or grid permanent forests in the outskirts. This could be due to the existence of small, long-standing tree patches that had a much greater chance of being preserved far from the city center and were not depicted on old maps. Although these micro-refuges may harbor individual forest species adequately, larger ancient and permanent forest areas are needed to maintain the higher number of forest specialists. Our results helped identify the areas most suitable for afforestation, considering the preservation of forest continuity and the migration possibilities of forest plants.